MIMR-DGSA: unsupervised hyperspectral band selection based on information theory and a modified discrete gravitational search algorithm - Tschannerl, Julius; Ren, Jinchang; Yuen, Peter W. T.; Sun, Genyun; Zhao, Huimin; Yang, Zhijing; Wang, Zheng; Marshall, Stephen (Elsevier, 2019)
Band selection plays an important role in hyperspectral data analysis as it can improve the performance of data analysis without losing information about the constitution of the underlying data. We propose a MIMR-DGSA algorithm for band selection by following the Maximum-Information-Minimum-Redundancy (MIMR) criterion that maximises the information carried by individual features of a subset and minimises redundant information between them. Subsets are generated with a modified Discrete Gravitational Search Algorithm (DGSA) where we definine a neighbourhood concept for feature subsets. A fast algorithm for pairwise mutual information calculation that incorporates variable bandwidths of hyperspectral bands called VarBWFastMI is also developed. Classification results on three hyperspectral remote sensing datasets show that the proposed MIMR-DGSA performs similar to the original MIMR with Clonal Selection Algorithm (CSA) but is computationally more efficient and easier to handle as it has fewer parameters for tuning.
Keywords: Band selection; Discrete optimisation; Entropy; Evolutionary computation; Feature selection; Gravitational search algorithm; Hyperspectral imaging; Maximum-Information-Minimum-Redundancy; Mutual information